Design evaluation of electrical power distribution system for Ghanim Al Thani holding office building, Doha, Qatar - Matinong, John Albert P. (Manila Professional Regulation Commission, 2015)
The technical engineering report give an emphasis to the design evaluation of the of electrical power distribution system of the office building for Ghanim Al Thani Holdings at Doha, Qatar. The project will be powered by 3 nos. of Dry Type Transformer, each rated of 1600kVA , 11/0.415kVv, 3Phase, 50Hz and it will be connected to low voltage switchgears (MV Panel-l, MV Panel-2, MV Panel-3) respectively. The scope of the report shall be focus on Transformer 3, MV Panel-3 and downstream to the various loads. The essential loads (Life Safety equipment such as Jet Fans, Extract Fans, Lifts, Fire Fighting equipment, emergency lights, Fire Alarm/Voice Evacuation Alarm system, access control system, car park ventilation system) are considered in accordance to the NFPA101 standards. These shall be energized by a 900kVA Standby Generator through the bus coupler in the MV Panel-3 during the Kahramaa power supply failure. The report will show the manual calculation using the basic formulas and design principles in electrical engineering for load calculations, sizing of electrical equipment panels, transformer sizing, sizing of feeder cables, circuit breaker sizing, voltage drop calculations, short circuit calculations(symmetrical & unsymmetrical), protection and insulation coordinations.
Technical report submitted in partial fulfillment of the requirements for the licensure examinations for professional electrical engineers.
E2-651G donated by Mr. Jaime V. Mendoza.
Keywords: Commercial buildings -- Electric equipment